Misallocation and Total Factor Productivity in Italy: Evidence from Firm‐Level Data. (2nd November 2015) - Calligaris, Sara
Abstract: Over the last two decades, total factor productivity (TFP) in Italy decreased by 0.2% per year, while increasing on average in the Euro‐area countries. This decline suggests the existence of large inefficiencies in the allocation of resources, making the Italian case particularly interesting and suitable in order to study the role of misallocation. In this article, I quantify the within‐industry misallocation of inputs in Italy over the period 1993–2011, by applying the Hsieh and Klenow's methodology. Using a micro‐level longitudinal dataset of Italian manufacturing firms, I find that, in the hypothetical absence of distortions, aggregate TFP in manufacturing would be boosted by 58% in 1993, by 67% in 2006 and by 80% in 2011. This leads to a twofold conclusion: first, misallocation plays a crucial role in determining the inefficiency level of the Italian manufacturing sector; second, misallocation has increased over time. Given the magnitude of the results obtained and the policy implications related thereto, I take a step ahead by checking to what extent the degree of misallocation can be attributed to specific characteristics of the Italian firms: it emerges that misallocation is higher for firms located in the south and at low‐technological intensity, as well as for small or young firms.